Monitoring Banjir Berbasis Wireless Sensor Network - Abdul Jahir; Kuat Indartono; Bagus Adhi Kusuma; Abdul Ghofur (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Flood disasters often occur in Indonesia. Banyumas Regency is one of the districts that often experiences flooding. The area with the flood-prone category is Sumpiuh sub-district. One of the villages that often floods is Pandak Village. Cases that often arise when it rains for a long time and after it stops only a few moments later floods occur. The purpose of this study is to provide early warning system of flood detection to residents, so that material losses can be minimized. This research was conducted by making a Wireless Sensor Network (WSN) based flood monitoring device. The device consists of sensor nodes and gateways connected to a star topology. The sensor node is equipped with a Long Range (LoRa) module and a laser sensor, at the gateway it is equipped with a LoRa, liquid crystal display (LCD) and a buzzer. Functional test results, the device works well. The laser sensor can measure water levels up to 150 cm and for a LoRa range up to 250 m. The gateway can receive data sent by LoRa and can display the laser sensor measurement results on the LCD and the buzzer can give a sound signal. The device can monitor the water level with the display of the water level in real-time on the LCD and the buzzer can sound according to four water level statuses are safe level, first alert level, second alert level and danger level.